Korelasi Faktor Sosial Ekonomi dan Tingkat Konsumsi Zat Gizi dengan Kejadian Stunting - Yoswenita Susindra; Reny Tri Wahyuningsih; Agustina Endah Werdiharini (Politeknik Negeri Jember, 2020)
Stunting (short) is an underweight nutritional condition measured based on height index by age (TB / U) compared to the standard, usually used in infants. This stunting condition (short), is an indicator of children's health that describes the incidence of under-nutrition that lasts for a long time (chronic) and is influenced by low levels of nutrient consumption and low socioeconomic. The purpose of this research is to know the correlation between socioeconomic factor and nutrient consumption level with stunting incident in underfive in work area of Kalisat health center, Jember regency. This research was conducted for two months by giving 24 hour food recall form, and form characteristic of respondent. The research design used cross sectional. The statistical test used is spearman test. From the spearman test result there is no relationship of mother education with stunting event (p=0,19), there is no relationship of father education with stunting event status (p=0,08), there is no relation of mother job with stunting event (p=0,95), there is no relation of parent income with stunting event (p=0,12), there is relation of number of family member with stunting event (p=0,00), there is no relation of energy consumption level with stunting event (p=0,59), there was no correlation of protein consumption level with stunting event (p=0,18), no correlation of calcium consumption level with stunting event (p=0,60), no correlation of zinc consumption level with stunting event (p=0,21).